Therapeutic hypothermia for neonatal encephalopathy in Indian neonatal units: A survey of national practices - Chandrasekaran,M; Swamy,R; Ramji,S; Shankaran,S; Thayyil,S (Indian Pediatrics, 2017)
This cross-sectional web-based survey suggests that cooling therapy is offered as standard of care for babies with neonatal encephalopathy in 10/25 (40%) of public and 37/68 (51%) of private level 2 or 3 neonatal units in India. 25 (53%) used locally improvised cooling methods, and the cooling practices differed from established protocols in high-income countries.